Analysis of the Needs for Developing E-Comic Media for Field Trips to Introduce Reading and Writing Literacy to Aud in Historical Tourism Exploration in Palembang - Purnamasari, Nuratni Agung; Sumarni, Sri; Safitri, Erna Retna (Lembaga Bale Literasi, 2026)
This study aims to analyze the need for developing e-comic learning media based on field trips to introduce reading and writing literacy to early childhood (AUD) through historical tourism exploration in Palembang. The background of this study is based on the low interest and ability of early literacy children and the still dominant use of conventional learning media in PAUD institutions. The study used a quantitative descriptive approach with a needs analysis design. The research subjects included teachers and students at TK Bina Putra 2 and TK Islam Adventure. Data were collected through questionnaires, interviews, and observations, then analyzed using descriptive statistics and qualitative analysis techniques. The results of the study indicate that literacy learning is still dominated by print media and conventional methods that are less interesting for children. Meanwhile, the results of the student needs analysis showed a very high level of need for visual, interactive, story-based, and audio-visual learning media with an average percentage reaching 84.5%. Teachers also expressed the need for digital learning media that is innovative, easy to use, and able to integrate the local cultural context. These findings confirm that the development of e-comic media for field trips based on local historical tourism is highly relevant and needed. Thus, this research provides an empirical basis for the development of contextual, interactive, and local culture-based learning media to improve early childhood reading and writing literacy more effectively and meaningfully.